Domestic workers and sexual harassment in India: Examining preferred response strategies. (July 2022) - Vijayalakshmi, Akshaya; Dev, Pritha; Kulkarni, Vaibhavi
Highlights: This study focuses on the sexual harassment experiences of women employed as domestic workers in the informal sector in India. The informal sector is characterized by a lack of policies on reporting and addressing sexual harassment. We find that sexual harassment models should take into account women's relational ties with their family, other workers and the relationships of the worker with multiple supervisors. Further, for policies and procedures to work, it is crucial to change the societal mindset around sexual harassment acceptance and reporting. Importantly, we need to reduce the burden of proof that a victim carries to make a credible case. Abstract: The purpose of this research is to understand how women working as domestic workers, who are part of the informal sector, are likely to respond to sexual harassment incidents. Unlike the organized sector, women in informal and nontraditional workspaces often do not have access to formal organizational mechanisms for lodging complaints, thus making it important to understand their response strategies. To understand their likely response to sexual harassment in the informal sector, we conducted a detailed survey of 387 domestic workers in India where we presented each respondent with eleven possible sexual harassment scenarios and nine possible responses to each such scenario. We find that (a) women are most likely to employ strategies that are self-focused and with minimal support from friends/family. (b) Women complain to authorities/family only when they can furnish evidence of harassment. (c) Women are not likely to complain to their female supervisor under any circumstances. And (d) unsurprisingly, poorer, and migrant women are likely to be more silent than women who are relatively better-off about harassment. The results, in brief, show a distrust of the current systems. By examining this informal and unorganized workspace, we offer a stronger theoretical understanding of employee responses to sexual harassment and provide practical suggestions.